Equilibrium and rhythm in Piet Mondrian’s Neo-Plastic compositions - Fallahzadeh, Ali; Gamache, Geneviève (Cogent OA, 2018)
An important modern artistic movement of the twentieth century is Piet Mondrian’s Neo-Plastic art and theory. From 1917 to 1944 and concurrent with the creation of his Neo-Plastic paintings, he explained his esthetic principles of Neo-Plasticism in writings, though posteriori to the act of painting. Although a majority of scholars acknowledges a parallel evolution between his paintings and writings, Mondrian’s art is usually analyzed based on his sources of inspiration such as Theosophy, Hegelism, Platonism, and De Stijl. Hence, this paper aims to use Mondrian’swritings,asa stand-alone lens of scrutiny, to examine his esthetic evolution between two groups of paintings in theory and practice. The first group is early Neo-Plastic paintings created between 1919 and 1921, while the second group is mature works painted between 1935 and 1937. This article demonstrates the esthetic development in Mondrian’s thought by showing the degrees of conformity of his art with the fourth and the fifth principles of Neo-Plasticism (written by Mondrian in 1926) in regard to the expression of “equilibrium” and “rhythm” as universal and dynamic. Overall, this article will further the previous discussion on the parallel evolution of Mondrian’swritingsandhispaintings.Thisarticle shows that when it comes to the expression of equilibrium and rhythm, there are more similarities between the fourth and the fifth principles with his early Neo-Plastic compositions (1919–1921). As such, Mondrian deviated, although only slightly, from the content of the fourth and fifth principles in his 1935–1937 compositions.